Analiz dinamiki uglovych charakteristik poperemennogo dvuchšažnogo klassiceskogo choda sil'nejšich lyžnikov - Novikova, N. B.; Zacharov, G. G.; Kotelevskaja, N. B. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The dynamics of angular characteristics and angular velocities of an alternate two-stroke course of elite skiers-racers at the distance of the World Cup 2016 is analyzed in the article. Criteria of efficiency of repulsion in the classical technique are determined: the beginning of active subsidence at the time of ski stop with simultaneous bending of the leg in the ankle and knee joints; at the beginning of repulsion the athlete`s feet are in the same plane and the angle in the knee joint is minimal; during repulsion, the angle of inclination of the shin remains unchanged, the rate of extension of the leg in the knee joint is maximal in the second half of the repulsion period (4.5-6 deg/s). The received data can be used for correction of stride technique in elite athletes.